Saúde mental e trabalho: a invisibilidade da doença mental nos benefícios previdenciários na região de Joaçaba/SC - Wames, Marisa Magali Maieski (2017)
The current study analyzed the social security benefits granted by the INSS agency in Joaçaba city, Santa Catarina State, in the year of 2016, in order to verify if the benefits granted to workers due to the mental illness were recognized as a result of the work performed or if the same trend verified in the years 2010 to 2012, when mental illness was only recognized in the illness benefits of any nature or cause, therefore, unrelated to the work done. This invisibility of mental illness in the benefits granted in relation to the work carried out, instigated us to study the work and the transformations that occurred in its processes in the last two historical periods, which means new requirements for the worker who has been physically ill, as was explicit in the Industrial era model led by the North American models, denominated Fordism and Taylorism, with international expansion. Physical illness continues in the model of work in contemporary capitalism known as the era of knowledge, whose worldwide expansion occurred from the model of Japanese industries, called toyotism, but its new requirements began to compete for the mental illness of the workers. These periods are theoretically based by authors such as Karl Marx, Krishan Kumar, Ricardo Antunes, Zygmunt Bauman, Richard Sennet, Robert Castel, among others. The research also listened to mentally ill workers and found out that these narratives pointed out several factors related to work that contributed to the constitution of mental illness, whose aspects were presented and analyzed in the research, corroborating with the theoretical basis studied, demonstrating the deepening of the precariousness of the work, and the aggravations for the mental illness not seen in the social security benefits in the region of Joaçaba city / SC.